Navigating Hepatitis C care: Knowledge gaps and access barriers among young women who inject drugs in rural Appalachia - Wagi, Cheyenne R.; McDowell, Renee; Wright, Anyssa; Egan, Kathleen L.; Meade, Christina S.; Young, April M.; Enderle, Madison N.; Estadt, Angela T.; Lancaster, Kathryn E. (PLOS ONE, 2025)
Background Hepatitis C virus (HCV) and injection drug use among young women are dramatically rising in the rural United States. From 2004 to 2017, heroin use among non-pregnant women increased 22.4% biennially, mirroring increases in HCV cases, especially among younger populations. Young women who inject drugs (YWID, ages 18–35) face elevated HCV risk due to biological, behavioral, and socio-cultural factors. Barriers to HCV testing and treatment services further delay diagnoses, fuel transmission, and limit access to harm reduction services. This study applies the Theoretical Domains Framework (TDF) to identify factors influencing HCV testing and treatment among YWID in rural Appalachia Ohio. Methods We conducted in-depth interviews with YWID (n = 30) in 2023 to understand their HCV testing and treatment experiences in rural Appalachia Ohio. Interviews were transcribed, inductively coded, and analyzed using grounded theory. Identified themes were mapped onto the TDF domains. Results Key TDF domains influencing HCV care included knowledge, beliefs about consequences, and intentions. While YWID knew where to get tested, they expressed uncertainty about treatment value and access while actively using drugs. Social influences, stigma, and mistreatment by healthcare providers created barriers to treatment. Environmental context and resources, such as transportation, also influenced access to care. Conclusions YWID in rural Appalachia face barriers to HCV care, such as gaps in knowledge about HCV treatment, which is compounded by gendered stigma, and logistical challenges. Rapidly changing treatment restrictions led to misinformation about treatment access. These gaps highlight the need for interventions specifically designed to address YWID lived experiences.